2022
DOI: 10.2340/actadv.v101.910
|View full text |Cite
|
Sign up to set email alerts
|

Guselkumab Treatment Outcomes and Persistence in a Nationwide Real-world Cohort of Patients with Plaque Psoriasis

Abstract: Guselkumab treatment outcomes and persistence were assessed in a real-world cohort of Finnish patients with difficult-to-treat plaque psoriasis over a median follow-up of 1 year. Data on 181 patients who initiated guselkumab at the 15 study centres were collected retrospectively from the patient charts. Prior exposure to biologic therapies was common with 56% and 35% having used at least 1 and 2 biologics, respectively. Median guselkumab treatment duration was 11 months with 21 patients (12%) discontinuing tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Eighty-five patients had a follow-up duration of at least 1 year and among them 73 (86%) were still on guselkumab at 1 year. 31 High improvements were seen in the absolute PASI scores with 32 patients having absolute PASI ≤ 2 after a 9–14-month treatment. 31 A prospective, observational, single-center, real-life study on 23 patients conducted by Megna et al demonstrated the efficacy and efficiency of guselkumab, showing that, at week 12, 95.6% of patients achieved PASI 75, while 43.5% PASI 90 whereas PASI 100 was reached by 26%.…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Eighty-five patients had a follow-up duration of at least 1 year and among them 73 (86%) were still on guselkumab at 1 year. 31 High improvements were seen in the absolute PASI scores with 32 patients having absolute PASI ≤ 2 after a 9–14-month treatment. 31 A prospective, observational, single-center, real-life study on 23 patients conducted by Megna et al demonstrated the efficacy and efficiency of guselkumab, showing that, at week 12, 95.6% of patients achieved PASI 75, while 43.5% PASI 90 whereas PASI 100 was reached by 26%.…”
Section: Methodsmentioning
confidence: 93%
“… 31 High improvements were seen in the absolute PASI scores with 32 patients having absolute PASI ≤ 2 after a 9–14-month treatment. 31 A prospective, observational, single-center, real-life study on 23 patients conducted by Megna et al demonstrated the efficacy and efficiency of guselkumab, showing that, at week 12, 95.6% of patients achieved PASI 75, while 43.5% PASI 90 whereas PASI 100 was reached by 26%. 32 Moreover, at week 44, PASI 75, PASI 90, and PASI 100 were reached by 95.6%, 73.9%, and 43.5% respectively.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…(PASI ≤ 3 in 65% and 79% and corresponding PASI ≤ 1 in 34.2% and 50.8% of patients after 3 and 7 months, respectively) [ 18 ], Mälköne et al. (PASI ≤ 2 in 80% of patients after 9–14 months) [ 19 ], and with modified NRI method by Del Alcázar et al. (PASI ≤ 4 in 78.4% and 80.1% and corresponding PASI ≤ 2 in 63.8% and 72.7% of patients after 4 and 6 months, respectively) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…PASI 90 and PASI 100 responses are considered the treatment goals in moderate-to-severe psoriasis, suggesting complete or nearly complete clearance, generally related to significant improvement in health-related quality of life. As a human monoclonal antibody targeting the p19 subunit of IL-23, guselkumab was the first antibody of its class to be approved for treating moderate-to-severe plaque psoriasis in adults (7)(8)(9)(10). In this study, guselkumab was administered as a 100-mg subcutaneous injection at weeks 0 and 4, and then at 8-week intervals.…”
Section: Discussionmentioning
confidence: 99%